2004
DOI: 10.1096/fj.04-2640fje
|View full text |Cite
|
Sign up to set email alerts
|

Anabolic signaling deficits underlie amino acid resistance of wasting, aging muscle

Abstract: The nature of the deficit underlying age-related muscle wasting remains controversial. To test whether it could be due to a poor anabolic response to dietary amino acids, we measured the rates of myofibrillar and sarcoplasmic muscle protein synthesis (MPS) in 44 healthy young and old men, of similar body build, after ingesting different amounts of essential amino acids (EAA). Basal rates of MPS were indistinguishable, but the elderly showed less anabolic sensitivity and responsiveness of MPS to EAA, possibly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

69
1,005
13
17

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,016 publications
(1,141 citation statements)
references
References 47 publications
69
1,005
13
17
Order By: Relevance
“…Interestingly, similar morphology, transcript and signalling processes were also observed in cells isolated from aged human muscle [33][34][35] and in whole tissue biopsies [36,37]. Thus, these cells can be used as a representative model to investigate mechanisms of atrophic phenotypes (PD) vs. parental control cells (CON) that display hypertrophic phenotypes [7].…”
mentioning
confidence: 71%
“…Interestingly, similar morphology, transcript and signalling processes were also observed in cells isolated from aged human muscle [33][34][35] and in whole tissue biopsies [36,37]. Thus, these cells can be used as a representative model to investigate mechanisms of atrophic phenotypes (PD) vs. parental control cells (CON) that display hypertrophic phenotypes [7].…”
mentioning
confidence: 71%
“…Future studies should investigate the autophagy pathway further. Cuthbertson et al (2005) reported that the major factor causing loss of muscle mass in ageing-related muscle atrophy is a reduction in protein synthesis rates. These researchers related this decreased protein synthesis to a decreased intramuscular expression and activation (phosphorylation) of signalling proteins.…”
Section: Potential Mechanisms Leading To Decreased Muscle Mass In Mirmentioning
confidence: 99%
“…Dietary protein intake stimulates muscle protein synthesis (MPS) and facilitates postprandial muscle protein accretion [105]. Moreover, the need for more dietary protein with ageing is in part due to a compromised ability to efficiently utilize amino acids for MPS, resulting in a blunted muscle protein synthetic response to an anabolic stimuli, a phenomenon termed anabolic resistance [105,106]. As of consequence, evidence based recommendations for protein intake in older adults have recently been published [107,108].…”
Section: Underlying Mechanisms Underpinning the Potential Benefits Ofmentioning
confidence: 99%